Development of a reference material for Staphylococcus aureus enterotoxin A in cheese: Feasibility study, processing, homogeneity and stability assessment. (1st February 2015) - Zeleny, R.; Emteborg, H.; Charoud-Got, J.; Schimmel, H.; Nia, Y.; Mutel, I.; Ostyn, A.; Herbin, S.; Hennekinne, J.-A.
Highlights: Reference materials are key for accurate measurements of Staphylococcus aureus enterotoxin A (SEA) in food. A feasibility study revealed a suitable way to process spiked cheese powders on a larger scale. Three candidate reference materials for SEA were processed. The materials exhibit suitable homogeneity and short-term stability for the intended use. Abstract: Staphylococcal food poisoning is caused by enterotoxins excreted into foods by strains of staphylococci . Commission Regulation 1441/2007 specifies thresholds for the presence of these toxins in foods. In this article we report on the progress towards reference materials (RMs) for Staphylococcal enterotoxin A (SEA) in cheese. RMs are crucial to enforce legislation and to implement and safeguard reliable measurements. First, a feasibility study revealed a suitable processing procedure for cheese powders: the blank material was prepared by cutting, grinding, freeze-drying and milling. For the spiked material, a cheese-water slurry was spiked with SEA solution, freeze-dried and diluted with blank material to the desired SEA concentration. Thereafter, batches of three materials (blank; two SEA concentrations) were processed. The materials were shown to be sufficiently homogeneous, and storage at ambient temperature for 4 weeks did not indicate degradation. These results provide the basis for the development of a RM for SEA in cheese.